Emergency Lateral Canthotomy Followed by Orbital Septum Release for Traumatic Retrobulbar Hemorrhage: 2 Case Reports - Yosuke Ochi, MD; Shimpei Ono, MD, PhD; Rei Ogawa, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Retrobulbar hemorrhage can increase intraorbital pressure, thereby elevating intraocular pressure (IOP), inducing ischemia, and/or threatening the optic nerve. Emergent decompression is needed to preserve visual function. Multiple decompression methods that are favored by different clinical departments have been reported. Here, we report 2 emergency room cases of retrobulbar hemorrhage that were treated first with lateral canthotomy and inferior cantholysis (LC/IC) under local anesthesia followed an hour later by wide orbital septum release under general anesthesia. LC/IC permits the quickest possible decompression after injury, thus temporarily reducing IOP. Orbital septum release consolidates the decompression by permitting hematoma drainage and identification and hemostasis of the bleeding point. In our cases, IOP dropped from 55 and 52 mm Hg to 14 mm Hg in both cases, and corrected visual acuity improved from light perception/counting fingers to 20/20. Notably, LC/IC was only conducted 7 and 4 hours postinjury. This counters the commonly held view that decompression should occur within 2 hours of injury to achieve visual recovery. Thus, even though LC/IC followed by orbital septum release requires 2 surgical steps, it can result in excellent visual outcomes after retrobulbar hemorrhage.